Early Domestic Dogs - Lawrence, Barbara (1967)
espec. 56-58, Part II: Old World Dogs (i. a. Çayönü, Diyarbakir, and Haditha, Iraq. Ancestry of Domestic Dogs (small figurines with curly tails from Jarmo).